Teacher who (cannot) Change: Experimental Processes of Physical Education Teachers by means of Pedagogical Innovations at the time of Their Professional Development - Alagül, Özlem; Gürsel, Ferda (Turkish Education Association, 2019)
It is known that innovations in the area of physical education at the beginning of the 20th century did not bring about any changes (Evans, 1985). In the meantime, teacher-centered approaches were preferred more even though there were numerous pedagogical alternatives (Ertan & Çiçek, 2003; Demirhan et al., 2008; Ince & Hunuk, 2010). According to Casey (2013), this situation occurred because new innovations still are a “talked about ‘future, rather than an “actioned‘ in physical education (Casey, 2013). It has been stated that one of the reasons why teachers cannot maintain innovations is their need of support (Bechtel & O’Sullivan, 2007). Therefore, this study aimed to investigate physical education teachers’ process of experiencing a pedagogical innovation in company with an expert in their professional development process. This qualitative study was designed in the form of participatory action research in order to support the use of Tactical Games Model (TGM) for one year among 7th grade students by two physical education teachers. In this study; teachers initiated professional dialogues with each other and with expert support, and then change is supported with individual teacher inquiries. Teachers were affected by the pedagogical model when they included TGM in their own practices. As a result, teachers are actively involved in the process of learning an innovation and facilitate the adoption of innovation with the help of other teachers and experts.
Keywords: Katılımcı eylem araştırması, Öğretmen öğrenmesi, Mesleki öğrenme, Pedagojik yenilik, Taktiksel oyun modeli; Participatory action research, Pedagogical innovation, Professional learning, Tactical games model, Teacher learning; 4. Education